Analysis of independent city concept in reclamation area PIK 1 & PIK 2 based on community, government, and private sector role - Marsella, Miranda Hetu; Putra, Putu Adhitya Dita (Interaction, Community Engagement, and Social Environment, 2024)
Reclamation is part of spatial planning to make coastal areas more useful, as well as to increase land resources from an environmental, social and economic point of view. The development of the PIK (Pantai Indak Kapuk) 1 and 2 reclamation areas is a concept of a sustainable Independent City. The role of the community, government and private sector plays an important role in developing the region. It is also necessary to pay attention to the environmental impact caused by reclamation activities. This study uses qualitative and quantitative methods with a descriptive analysis approach by collecting data from review articles, questionnaires and using maps via satellite imagery. Through the participation of the role of the community which is divided into the general public, fishing communities, and affected communities explaining the interrelationships where the general public's perception of the most supporting parameters for independent cities is infrastructure and land use, then fishing communities have an impact on fish catches, as well as affected communities experiencing rejection resulting in a change in livelihood. The government's role in regulatory planning as a regional spatial plan includes planning processes, infrastructure, public services and a sustainable environment. The role of the private sector can be seen from the planning and development process which chooses to build supporting infrastructure such as tourist centers, shops, public transportation and other facilities. CSR programs by private parties or developers are one of the efforts to contribute positively to the environment and surrounding communities. Correlation of independent cities with land use from planning, development and development processes that reflect the commitment and role of the community, government and private sector seen in 1995, 2014, 2023 The concept of balance and independence in independent cities emphasizes the importance of a holistic approach in urban planning and management. PIK 1 & 2 reclamation areas based on independent cities based on the role of the community, government and private sector in regional development are the key to achieving sustainable development.